THE EFFECT OF DEBT TAX SHIELD AND NON DEBT TAX SHIELD ON CAPITAL STRUCTURE ON ADVERTISING PRINTING MEDIA COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Tengku Eka Susilawaty (Enrichment : Journal of Management, 2021)
To measure the proportion of debt and equity used as a source of company funding, it can be seen from the capital structure because the capital structure is a comparison between debt and equity. This study aims to examine the debt tax shield and non-debt tax shield on the capital structure of advertising printing media companies listed on the Indonesia Stock Exchange. The research approach used in this study is associative. The sample used is a saturated sample of 13 companies for the year 2017-2019. The data analysis technique used is descriptive statistics, multiple linear regression test of panel data model, hypothesis testing (t-test and F-test) and coefficient of determination test. The results of this study indicate that partially debt tax shield and non-debt tax shield have an effect on capital structure. Then the debt tax shield and non-debt tax shield simultaneously affect the capital structure. Thus, decision makers can consider these ratios as a tool of consideration in making policies in the tax system in companies.